Dispersion properties of plasmonic sub-wavelength elliptical wires wrapped with graphene - Cuevas, Mauro (2021)
One fundamental motivation to know the dispersive or frequency dependent characteristics of localized surface plasmons (LSPs) supported by elliptical shaped particles wrapped with a graphene sheet, as well as their scattering characteristics when these elliptical LSPs are excited, is related to the design of plasmonic structures capable of manipulating light at sub-wavelength scale. The anisotropy imposed by ellipse eccentricity can be used as a geometrical tool for controlling plasmonic resonances. Unlike the metallic case, where multipolar eigenmodes are independent of each other, we find that the induced current on a graphene boundary couples multipolar eigenmodes with the same parity. In the long wavelength limit, a recursive relation equation for LSPs in terms of the ellipse eccentricity parameter is derived, and explicit solutions at lowest order are presented. In this approximation, we obtain analytical expressions for both the anisotropic polarizability tensor elements and the scattered power when LSPs are excited by plane wave incidence.